ANALISIS YURIDIS LEGALITAS CRYPTOCURRENCY SEBAGAI ALAT PEMBAYARAN DALAM TRANSAKSI BISNIS DI INDONESIA - Selviana Margaretha; Elfrida Ratnawati (UNES Law Review, 2023)
Abstract The flow of world globalization has greatly impacted technological advances, especially in the payment technology sector which can assist in a fast, safe and secure payment system. At this time we have realized that there is a named currencycryptocurrency, but in Indonesia it has not been regulated concretely regarding the use and legal protectioncryptocurrency. This study aims to examine the regulation of legality and legal protection of cryptocurrencies based on laws and regulations and policies made by the Indonesian government using normative juridical law methods and statutory regulations approaches. Regarding the legal materials used by the authors in the form of primary and secondary legal materials obtained by the authors from books, journals, literature, and data from the Indonesian Government, then the authors analyzed the data using descriptive and legal arguments to obtain systematic and comprehensive research results. Regarding the results of the research, it explains that Cryptocurrency in Indonesia has not been fully regulated, but several rules and policies have been issued by the authorities. Bank Indonesia prohibits the use of Cryptocurrency as a legal means of payment, but the use of Cryptocurrency as a digital asset is still permitted. Bappebti regulates Crypto exchanges, DGT regulates taxes on profits from Cryptocurrency transactions, and OJK warns the public about the risks of investing in the Crypto market. The Indonesian government is in the process of regulating cryptocurrencies more comprehensively through revisions to the capital market law and tax laws.